Songs as Media in Teaching Pronunciation: A Descriptive Study at English Course in Pare - Muhammad Arief Zuliyan (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
This research is to examine how the implementation of English songs is as media in teaching pronunciation at Kampung Inggris (English Village) course in Pare Kediri. The researcher uses descriptive qualitative case study design. The researcher has to make sure that they conducted everything themselves from gaining access to the left field. In this study, the researcher acts as an observer. The researcher collects the data and reports them descriptively based on the situation and events in the field. After then, it obtains the data by observation in the pronunciation class in the Kampung Inggris (English Village) course twice, interview with seven informants, and documentations, which consist of photos, recordings, and video. The result shows that the implementation of English songs as media in teaching pronunciation at the Kampung Inggris (English Village) course is run well. The results of the study are obtained from the observation and interview from some informants in Kampung Inggris (English Village) course; they described as follows the conclusion of teaching pronunciation by using English songs. It also makes the learners confident to speak the English language. So, they can pronounce like a native as well.